Practical Implementation of the BLW Method During the Expansion of the Infant Diet—A Study Among Polish Children - Białek-Dratwa, Agnieszka; Szczepańska, Elżbieta; Trzop, Paulina; Grot, Martina; Grajek, Mateusz; Kowalski, Oskar (Frontiers in Nutrition, 2022)
The aim of the study was to verify the knowledge of mothers of children under 3 years of age about the Baby Led Weaning (BLW) feeding model and their practical implementation of this method. The study involved 761 mothers and their children. After analysis of the inclusion and exclusion criterion, the information provided by women 699 aged 21–48 years was included in the final data analysis. In the study group, most children were breastfed for 6 months to 1 year (n = 256, 36.7%), 1 year to 2 years (n = 179, 25.6%) and over 2 years (n = 71, 10.2%). Starting dietary expansion before 17 weeks of age was implemented in 47 (6.7%) children, between and 17–26 weeks of age in 328 (46.9%) children, and after 26 weeks of age in 324 (46.3%) children. Feeding food and dishes from the family table was practiced by 518 (74.1%) mothers. Spoon-feeding was practiced by 529 (75.6%) children, 157 (22.4%) children were fed this way sometimes. Taking into account the above data, feeding with the BLW method was used in 170 children (24.2%). In the examined group of mothers the use of the BLW method in feeding their children, especially during diet expansion, was declared by 408 women (74.8%). The child's independent decision concerning what the child will eat and what is according to the BLW method is accepted by 434 (62.1%) mothers. Among the positive aspects of using the BLW method, the women surveyed indicated the child's independence, while among the disadvantages, the omnipresent mess and chaos when eating meals.